الوسطية في الإسلام وعلاقتها بالأمن الفكري : "دراسة تأصيلية في ضوء القرآن الكريم " - Awad Ibrahim Ali, Hanan (Jurnal Studi Al-Qur'an, 2020)
This research included the concept of the security and its meanings in the Noble Quran, and also clarified the term Medial (Al-Wasatya) in language and idiomatically, and mentioning the Proofs, and demonstrate the general characteristics of it, and show the firm relationship between the Medial method and achieving the intellectual security. The Medial realized in the Islamic Nation, that it is the better of all nations, and the most equitable and medial, because it belonged to the most might methods and the most better legitimate that Allah To Whom is ascribed all perfection and majesty, and accepted it as a religion. So intellectual security means the protection of the religious, cultural, moral, and security systems in confrontation with each thought, or perverted belief, or extreme, and what followed of behavior. This meaning achieves the comply with the Medial because it prevents the excessiveness that affects the thought and makes its owner intellectually perverted. The study clarified the extent of Islam's concern about psychological and intellectual security and its strong correlation with sound thought and faith